Determinasi Penyebab Stunting dan Persepsi Sosial terhadap Resiliensi Keluarga di Kecamatan Gadingrejo Pasuruan - Yuanda, Baretha; Rozakiyah, Desy Santi (Institut Teknologi Sepuluh Nopember, 2024)
Stunting as a malnutrition problem signifies a gap in human development, so it is included in the 2nd SDGs indicator. The study aims to determine the influence of the causes of stunting and social perceptions on family resilience in Gadingrejo Subdistrict, Pasuruan City because the prevalence of stunting is 11.7% in 2023. The sample amounted to 80 families of stunted children represented by mothers. Data were collected through questionnaires, multiple regression analysis, and analyzed with Robert Putnam's social capital theory. A total of 373 children (February 2024) in Gadingrejo subdistrict were stunted. The analysis showed that the causes of stunting had a significant effect on family resilience with a p value of 0.000, while social perceptions had no significant effect on family resilience with a p value of 0.115. The causes of stunting and social perceptions have a significant effect on family resilience with a p value of 0.000.